Prospective observational study in comorbid patients with chronic lymphocytic leukemia receiving first-line bendamustine with rituximab. (April 2019) - Špaček, Martin; Obrtlíková, Petra; Hrobková, Stanislava; Cmunt, Eduard; Karban, Josef; Molinský, Jan; Šimkovič, Martin; Mociková, Heidi; Mohammadová, Lekaa; Panovská, Anna; Novák, Jan; Trněný, Marek; et al.
Highlights: Bendamustine and rituximab is effective frontline therapy for comorbid CLL patients. ORR was 88%, CR rate 21%, and median PFS 36 months. Grade 3/4 hematological toxicity occurred in 55% of patients. Severe infections occurred in 15% of patients. Abstract: Chemoimmunotherapy with bendamustine and rituximab is an alternative treatment for elderly patients with CLL. The aim of this observational multicenter study was to prospectively assess efficacy and safety of bendamustine and rituximab in front-line therapy in patients with CLL and significant comorbidities in real hematological practice. Eighty-three consecutive patients with cumulative illness rating scale (CIRS) >6 who received at least one cycle of BR as first-line treatment were included in the study. The median age was 71 years (range, 53–83), the median CIRS was 8 (range, 7–17), and 60.2% of patients had a creatinine clearance ≤70 mL/min. FISH analysis, available for 78 cases, showed a del(17p) in 11.5% and del(11q) in 20.5% of patients. Overall response rate was 88.0% with a complete response rate of 20.5%. With median follow-up time of 22 months, the estimated median progression free survival was 35.9 months. Progression free survival and overall survival rates at 2 years were 69.9% and 96.2%, respectively. Grade 3 or 4 neutropenia, thrombocytopenia, and anemia were documented in 40 (48.2%), 14 (16.9%), and 8 (9.6%) patients, respectively. Grade 3 or 4 infections occurred in 14.5% of patients. Chemoimmunotherapy with BR is an effective therapeutic option with manageable toxicity for the initial treatment of CLL patients with significant comorbidities. ClinicalTrials.gov Identifier: NCT02381899.